Avant projet pour la sauvegarde de la race bovine Kouri et l'extension de son elevage a l'ensemble du perimetre du lac Tchad - Renard, P. (1972)
Existing status of Kouri rearing in Lake Chad basin was investigated. Data on breeding ability, animal disease, animal distribution, population and body measurements of oxen, bulls and cows included. Establishment of breeding centre and project financing scheme proposed.